Oxidation of the 5’-Position of Adenosine Analogues - B. Shejul, Pravin; H. Kadam, Nitin; V. Vyavahare, Amol; B. Kasawar, Gajanan; L. Panpaliya, Prashant (Asian Journal of Chemistry, 2018)
This article has been withdrawn at the request of the editor and publisher. The publisher regrets tha an error occurred due to plagiarism. The editor as well as publisher apologizes to the readers for this unfortunate error.